A INFLUÊNCIA DA ESTRATÉGIA DE FAMILIARIZAÇÃO LEXICAL NO PROCESSO DE INFERÊNCIA DE PALAVRAS-CHAVE - Souza, Maria Helena Guimarães Marques de (Intercâmbio, 2010)
The biggest problem in the reading of texts in English, according to the students is their lack of vocabulary. The aim of this paper is to study the strategy of lexical inference, based on contextual clues offered by an author of technical texts. The research investigated six categories of lexical familiarization proposed by Bramki & Williams (1984): exemplification, explanation, definition, stipulation, synonym and illustration. The subjects were 51 students of a technical course in Electronics and two texts were used in the research: one text about a subject already studied by the informants and another one about a supposed unknown subject, i.e., not studied in the specific area. The analysis of the results showed that the strategy of context is more used when the subjects do not have previous knowledge about the content of the text.